Associations between Engagement Types, Outcome Behaviors, and Quality of Life for Adults with Dementia Participating in Intergenerational Programs. - Janke, Megan C.; Purnell, I'Yanna; Watts, Clifton; Shores, Kindal (Therapeutic Recreation Journal, 2019)
Research has suggested that intergenerational interactions have the potential to improve the quality of life for adults with dementia. However, few studies have examined what type of interactions in intergenerational programs may drive well-being. This study examined the outcomes of participation in an intergenerational program (IGP) among adults who reside in a shared site facility with daily IGP activities. The study observed adult participation and engagement in these intergenerational activities and explored the association between engagement patterns and quality of life using the Menorah Park Engagement Scale (MPES) and Quality of Life (QOL) in Dementia Scale (QUALID). Results indicated a significant relationship between some of the engagement types and behavioral outcomes during the IGPs as well as significant correlations between types of engagement and behavioral outcomes and QOL for participants. Implications for recreational therapists working with dementia populations are discussed.